TANTANGAN INDONESIA DALAM MEWUJUDKAN PERTAHANAN DAN KEDAULATAN PANGAN - Naufal, Muhammad Faris (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The Second Principle of Pancasila mandates that Indonesia is a nation state that is independent, united, and sovereign, yet not chauvinistic. In this context, Indonesia remains part of the international community of nations and actively engages in equal and respectful global cooperation. This interpretation aligns with the classical conception of international relations, which asserts that all nations stand equal before international law and that no supranational authority holds power over sovereign states. Therefore, international relations should be based on equality, mutual respect, and non-intervention. As a member of the international society, Indonesia holds the responsibility to uphold human rights and foster a civilization grounded in decency and global brotherhood.